PERANCANGAN APLIKASI MEMBANTU MENCARI PELATIH DALAM BEROLAHARAGA BERBASISKAN MOBILE - Ferdianto, Ferdianto; Surja, Stephanie; Khansa Alifa, Fattiya Calista; Maharani, Swietenia; Setiyoko, Falih Muqsith (Infotech: Journal of Technology Information, 2022)
Sport is an activity that is easy to do, but sometimes we need someone to direct us so that the exercise we do can provide maximum benefits. Along with the number of active smartphone users of more than 100 million people and internet users in Indonesia reaching 175.4 million with a presentation reaching 64% of the total population, this creates business opportunities on the internet, especially in terms of sports. This research discusses the design of applications engaged in sports, especially in the field of hiring sports trainers. The purpose of this research is to analyze, plan business, design and create applications based on mobile applications. This application sees an opportunity in the use of information and communication technology in the field of sports, to increase user interest in sports applications. In addition, this will also have an impact on increasing community participation in sports activities. The method that the writer uses to collect data is library research, questionnaires and interviews. The results of this study are that the application has features that make it easy for customers to carry out sports activities and also understand sports material.